Pusa Pulu dalam perspektif masyarakat Akoon - Samallo, Jovico Onis (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2022)
This paper aims to analyze the understanding of the Akoon community on Nusalaut Island regarding the sacred site of Pusa Pulu. The focus is on the community's activities at Pusa Pulu, which are an integral part of life on Nusalaut Island. Pusa Pulu has also witnessed the encounter between culture and religion, which the community interprets as part of their local cosmology. The cultural and religious approaches of Jack David Eller and Chris Jenks are used to analyze the understanding of Pusa Pulu. A qualitative research method with an ethnographic approach was employed, and data were collected using interviews and literature reviews. For the Akoon community, Pusa Pulu is considered, first, a dwelling place for the ancestors of Nusalaut; second, a sacred site; third, a place that humbles everyone in the community; and fourth, a place of encounter with God as part of the reproduction of culture.